Kajian Potensi Pemanfaatan Limbah Sisik Ikan Dari Usaha Ikan Tangkap Laut (Studi Kasus Pasar Kota Bengkulu) - Wica Elvina; Risnita Tri Utami (Jurnal Kelautan, Lingkungan, dan Perikanan, 2022)
The potential utilization of fish by-products from fishery processing businesses in the form of fish scales can still be utilized for various synthetic products. Fish scales contain 29.8 – 40.9% protein; fat content 0.1-1%, mineral content 30.0-36.8%, collagen 37.5%, with the content of these protein compounds, fish scales can produce active compounds such as chitosan, collagen and gelatin. Bengkulu City is an area that has a major contribution to the province Bengkulu, with a total production of 46,145 tons of marine catch per year (KKP, 2020). This research aims to determine the potential of fish scales produced from fish processing activities in Bengkulu City based on the yield of fish scales per total weight of fish. Snapper, grouper and pomfret are the three types of marine capture fisheries could produce the highest production volume in Bengkulu City. Based on the research conducted, it was found that the yield of snapper scales resulted in the highest yield of fish scales, was 5.2% per total weight, with the results of the yield, it was known that fish scales could be utilized and potentially reprocessed into new products. The results of interviews with fish processing entrepreneurs in one of the largest markets in Bengkulu City (Panorama Market), it is known that every day the fishery product processing can produce 20-50 kg of snapper, so if this related to the yield of fish scales with the amount of fish production, it is known that Snapper scales have high potential to be used to provide additional income for fisheries entrepreneurs. The fish scale waste obtained can be reprocessed into useful products such as gelatin, chitosan, and collagen. Gelatin is used as a food additive, chitosan is used as a natural preservative, and collagen is used as an additive in food or pharmaceutical products.